(untitled) (Medical Forum Monthly, 2024)
Objective: To find out outcomes of pterygium excision with sutureless, glue free conjunctival auto graft. Study Design: Observational / descriptive study. Place and Duration of Study: This study was conducted at the Ophthalmology Department Unit-I, Dow University of Health Sciences, Civil Hospital Karachi from June 2011 to May 2015. Materials and Methods: Either gender patients above 25 years of age enrolled for primary pterygium excisionfollowed by limbal to limbal orientation of conjunctival auto graft without suture or adhesive glue. Recurrent pterygia, pseudo pterygia, ocular surface disorders, vascularized cornea, dry eye and patients already on topical anti metabolites were not included. Follow up was scheduled on 1st day, 1st week, 1st, 3rd, and finally 6th months.Chi square test was applied to check significance of recurrence with age, gender, occupation and graft size or graft application time. Results: Out of 382 participants, 303 (79.3%) were males. Majority of patients (77.7%) were young between 25 to 45 years of age. Mean time required for graft application was 16.89 ± 2.58 (std) minutes. Recurrence of pterygium was found in 32 (8.4%) cases. No significant relationship of recurrence of pterygium was found with other variables like gender, age, occupation, graft size or graft application time. Conclusion: Natural healing tendency of vascularized conjunctiva allow graft to adhere underlying scleral bed while well aligned autograft margins and limbal to limbal orientation do not allow overgrowth of fibrovascular conjunctival tissue thereby prevent recurrence of pterygium.